1H and 13C NMR spectra of Strychnos alkaloids: Selected NMR updates. Issue 19 (2nd July 2020) - Semenov, Valentin A.; Samultsev, Dmitry O.; Krivdin, Leonid B.
Abstract: The PBE0/pcSseg‐2//pcseg‐2 calculations of 1 H and 13 C NMR chemical shifts were performed for a classical series of 12 Strychnos alkaloids (except for the earlier studied parent strychnine), namely akuammicine, isostrychnine, rosibiline, tsilanine, spermostrychnine, diaboline, cyclostrychnine, henningsamide, strychnosilidine, strychnobrasiline, holstiine, and icajine. It was found that the calculated 1 H and 13 C NMR chemical shifts show markedly good correlations with available experimental data, as characterized by a mean absolute error of 0.22 ppm for the range of 8 ppm for protons and 1.97 ppm for the range of 180 ppm for carbons. Complementarily, the present results provide essential NMR update and fill a gap in the NMR data of this distinguished group of vitally important natural products. Abstract : The PBE0/pcSseg‐2//pcseg‐2 calculations of 1 H and 13 C NMR chemical shifts were performed in a series of 12 classically known Strychnos alkaloids. It was found that the calculated 1 H and 13 C NMR chemical shifts show a markedly good correlations with available experimental data, providing an essential NMR updates and filling a gap in the NMR data of this distinguished group of vitally important natural products.